Kajian Psikolinguistik: Pengaruh Virtual Engagement dalam Proses Belajar Mengajar Online - Oktavia, Wahyuni; Rossydi, Ahmad; Kurnianto, Benny (Politeknik Penerbangan Makassar, 2021)
This research is based on an understanding of the importance of having a positive influence by the students in online learning activities in terms of a Covid 19 pandemic. However, in fact, there are still many students who have behaviors that reflect the low level of student involvement in online learning. This study aims to determine the influence of virtual engagement and student perceptions in online learning. Respondents in this study were cadets of TLB 8 and 8 alpha cadets at the Makassar Aviation Polytechnic. The method used is descriptive qualitative. The results of this study indicate that the provision of virtual engagement in the online teaching and learning process is very influential, that is, it can help students in the online teaching and learning process where student engagement needs are met from external factors (structure, autonomy support, and involvement) and internal factors (need for relatedness, need for competence, and need for autonomy). The perception of the Makassar Aviation Polytechnic cadets regarding virtual engagement in the online teaching and learning process in this pandemic era is very helpful, enjoyable, increases motivation, and trains discipline